A simplified method for the determination of fenpropathrin residues in fruits - Navickiene, S.; Polese, L.; Minelli, E. V.; Ribeiro, M. L. (Vieweg, 1999)
A simple and efficient method is described for the determination of fenpropathrin in oranges, pears, apples and strawberries. The procedure: is based on the extraction of each homogenized fruit sample with hexane:acetone (1:1, v/v) mixture, followed, by a cleanup technique on a column packed with florisil, using a hexane:ethyl ether (7:3, v/v) mixture, and gas chromatographic, analysis with electron capture detection (ECD). The fortification levels (0.5; 1.0; 2.0 mg kg(-1)) were selected according to the maximum residue limits (MRLs) established for fenpropathrin by Brazilian legislation. Mean recoveries from five replicates of fortified fruit samples ranged from 83 % to 98 %, with:coefficients of variation from 1.4 to 13.5 and detection limits varying from 0.1 to 0.2 mg kg(-1).
Keywords: gas chromatography; pyrethroid pesticide residues; fenpropathrin; fruits